Performance of Potato Variety Rolpa Local (Solanum tuberosum L.) under Different Mulching Conditions and Zinc Levels at Rolpa, Nepal - Aryal, Muna (2023)
Use of the right mulching techniques is a crucial first step in replacing the issues with irrigation and weed infestation in potato production. To assess the performance of potatoes at two doses of zinc under different mulching conditions, a field experiment was laid out in a two-factorial, randomized complete block design (RCBD) comprising eight treatments with three replications each. The variety used was Rolpa local. The first factor consisted of three mulching materials: plant residue (M1), black plastic (M2), silver on black plastic (M3), and a control plot (M0), whereas the second factor compromised two levels of zinc (0 kg/ha and 4 kg/ha). Both plastic mulches were found to have a significant influence on germination rate during the field research; however, all other observations for growth and yield parameters, such as plant height, tuber number, tuber weight, and yield per plant, were significantly superior in the silver on black plastic. The highest germination percentage was observed in black plastic mulch (94.67 %). However, all other observations for growth and yield parameters were found to be significantly superior in the silver on black plastic mulch condition, with plant height (87.28 cm), leaf count (145.70), number of tubers per plant (22.16), and a total yield of 21.83 t/ha. Similarly, all the yield-attributing characters were found to be significantly different among zinc levels, with the highest total yield of 17.70 t/ha at 4 kg/ha of zinc. Silver on black plastic mulch and 4 kg/ha of zinc level resulted in the highest benefit-cost (B:C) ratios of 3.18 and 2.23, respectively. The results showed that using silver on black plastic mulch with a zinc level of 4 kg/ha improved both vegetative growth and potato yield, with favorable B:C ratios resulting in higher profitability. Thus, to maximize profit, it would be advantageous to utilize silver on black plastic mulch with 4 kg/ha of zinc.